Management of the Integration of the Al-Qur'an High School Curriculum with the Halaqoh Program of the Tribakti At-Taqwa Islamic Boarding School - Faqih, Nur Abdillah; Ehwanudin, Ehwanudin; Setiawan, Agus (CV. Bimbingan Belajar Assyfa, 2025)
This study was motivated by the dualism between formal school systems and pesantren education, which often operate separately and result in the lack of integration between academic learning and religious development of students. This study aimed to analyze the management of curriculum integration between SMA Al-Qur’an and the halaqoh program at Pondok Pesantren Tribakti At-Taqwa. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation. Data analysis used the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The results show that curriculum integration was implemented through management functions, including planning, implementation, and evaluation in an integrated manner. This integration harmonizes formal learning activities with halaqoh programs, which significantly improves educational quality in terms of academic achievement, religious understanding, and character development. Furthermore, the success of integration is supported by strong coordination among educators and a conducive pesantren environment.